Thermal structure above the Perth Canyon reveals Leeuwin Current, undercurrent and weather influences and the potential for upwelling. - Rennie, Susan; McCauley, Robert; Pattiaratchi, C. (CSIRO Publishing, 2006)
The Perth Canyon is a focal feeding area for pygmy blue whales on the Western Australian coast. Studies aimed at elaborating oceanographic mechanisms within the canyon were conducted between 2002 and 2005. Strings of temperature loggers set around the canyon rim were used to examine the water column’s response to climatological forcing, current meanders, upwelling and downwelling. Six moorings were positioned on a plateau in 500 m of water on the northern canyon rim, and one was positioned at the canyon head. Loggers were positioned to sample the whole water column, including the Leeuwin Current and Undercurrent. Moorings revealed spatial temperature differences between the plateau and canyon head. Observed temperature features ranged temporally from seasonal to <1 day. Seasonal changes in water temperature agreed with published Leeuwin Current studies: for example, mixed layer and stratification changes were apparent. Other observed temperature changes were related to Leeuwin Current movement and wind forcing such as the summer sea breeze and winter storms. Storms induced mixing, re-stratification, downwelling and upwelling as the wind changed direction and strength. Changes lasting a day were associated with diurnal sea breezes, internal waves and possibly solitary waves. Bottom loggers indicated that upwelling and downwelling events each occurred up to 20% of the time.